A rude awakening: post-take ward round in the department of medicine for the elderly. - Coni, N (1998)
This paper describes the post-take ward round of a department of medicine for the elderly (DME), to portray the nature of the medical admissions and their immediate management. The data concern the patients seen by one consultant in 28 such ward rounds during the last four months of 1997, in a teaching hospital where the DME is separate from the department of general internal medicine. 254 patients were seen, 107 men and 147 women, with an average age of 82.4 years (range 73-102). The decisions taken included diagnosis, further investigations, treatment, referral, discharge, and resuscitation status. Very few admissions were judged inappropriate, particularly among the majority referred by general practitioners. 101 patients were thought suitable for transfer to the department of general internal medicine, 109 definitely unsuitable. These findings support the view that, if medical beds are to be freed, the initiative must come from facilitating discharge rather than curtailing admission. Generalists are needed to sort and manage these patients. In the UK, these will often be general internal medicine consultant geriatricians, while the younger patients are seen by consultants practising general internal medicine in addition to one of the specialties. Sizeable numbers of these consultants are needed if the post-take ward round is to be efficient and not conflict with their fixed commitments.